To determine the truth of the equation \( 7 - \frac{4 \cdot 7^{3/49}}{\sqrt{7}} = 7 \), let's simplify the left side:
First, recall that \( \sqrt{7} = 7^{1/2} \). Hence, we can rewrite the equation as:
\[ 7 - \frac{4 \cdot 7^{3/49}}{7^{1/2}} \]
Applying the Quotient Property of exponents, which states \( \frac{a^m}{a^n} = a^{m-n} \), we have:
\[ \frac{4 \cdot 7^{3/49}}{7^{1/2}} = 4 \cdot 7^{3/49 - 1/2} \]
Now, convert \( 1/2 \) to a fraction with a denominator of 49: \[ \frac{1}{2} = \frac{49}{98} \]
So we can rewrite it: \[ 1/2 = \frac{24.5}{49} = \frac{48/49}{1} \]
Now, we calculate \( 3/49 - 24.5/49 \): \[ 3/49 - 24.5/49 = \frac{3 - 24.5}{49} = \frac{-21.5}{49} \]
Hence:
\[ 7 - 4 \cdot 7^{-21.5/49} \]
We can now rewrite the expression: \[ 7 - 4 \cdot 7^{-21.5/49} = 7 \]
This indicates that \( 7 - \) some positive quantity (since \( 7^{-21.5/49} \) is a fraction and multiplying by 4 keeps it positive) will NOT be equal to 7.
Therefore, the original statement is false.
The appropriate justification is:
False. When applying the Quotient Property, the final exponent is not 1.